PENGARUH MOTIVASI, DISIPLIN, DAN ETOS KERJA TERHADAP KINERJA GURU SLTA NEGERI DI KECAMATAN BAOLAN KABUPATEN TOLITOLI - Marlina, Marlina (Katalogis, 2015)
The research is aimed to: 1) explore and analysis simultanneous effects of motivation, discipline, and work ethos on teachers’ performance in public high schools in Baolan District of Tolitoli Regency; 2) explore and analysis significant effects of motivation on teachers’ performance in public high schools in Baolan District of Tolitoli Regency; 3) explore and analysis significant effects of discipline on teachers’ performance in public high schools in Baolan District of Tolitoli Regency; 4) explore and analysis significant effects of work ethos on teachers’ performance in public high schools in Baolan District of Tolitoli Regency. This research is descriptive causal with 141 population and 104 samples. The method of analysis is multiple linear regressions supported by SPSS program for windows version 21. Based on the result, it can be concluded that: 1) motivation, discipline, and work ethos simultaneously have significant effects on teachers’ performace in public high schools in Baolan District of Tolitoli Regency; 2)motivation significantly effects teachers’ performance in public high schools in Baolan District of Tolitoli Regency; 3) discipline significantly effects teachers’ performance in public high schools in Baolan District of Tolitoli Regency; 4) work ethos significantly effects teachers’ performance in public high schools in Baolan District of Tolitoli Regency.